PENGARUH SENAM YOGA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI KELURAN KAMPUNG JAWA WILAYAH KERJA PUSKESMAS TANJUNG PAKU KTA SOLOK TAHUN 2017 - Kurniati Maya Sari Netty Herawati (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The purpose of the study was to identify the influence of yoga gymnastics on the decreaseof blood pressure in elderly with hypertension in Kampung Jawa sub-district in TanjungPaku public Health Center service Area of Solok City in 2016. This research type is quasiexperiment with research design One group pretest post test design with sample number 13people with technique of purposive sampling. The results showed that the average systolicblood pressure before classical music therapy was 153.08 mmHg and after classical musictherapy there was a decrease in systolic blood pressure where the mean systolic bloodpressure was 142.31 mmHg with p-value = 0.000 (<0, 05). This number indicates thatthere is a significant effect between systolic blood pressure before and after yogagymnastic therapy. It is expected that elderly patients with hypertension know the benefitsand apply yoga exercises that can smooth blood flow, It is expected to facilitate nursingcare in people with high blood pressure using yoga practice as a complomenter treatment.Keywords: gymnastic yoga, elderly, hypertension, blood pressure